Dampak Pembelajaran Jarak Jauh Terhadap Pembelajaran Siswa di RA Darul Qur’an Desa Megu Gede Kabupaten Cirebon - Muslimah Muslimah; Hikmah Maulidiyanah; Inayahtul Maula (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2021)
The Covid-19 pandemic has had a huge impact on the development of education in Indonesia. Education in Indonesia enforces a distance learning program (PJJ) during the Covid-19 pandemic. This distance learning is implemented with the aim of reducing the spread of the covid-19 virus. The purpose of this study was to describe the impact of distance learning on student learning in RA Darul Quran MeguGede, Cirebon Regency. This research uses descriptive qualitative research. Data collection techniques use observation, interviews and documentation. Based on the research results, distance learning has a positive and negative impact on student learning. The positive impacts include children having a lot of time to study at home with their families, children learning about technology. In addition there are several negative impacts of distance learning (PJJ), namely, children have difficulty concentrating, children are more easily bored, children tend to feel bored because parents tend to demand that children be able to understand learning, children prefer to play than study, and students do not optimally. receive learning material because the teacher is less prepared in providing long-distance chasing and the condition of the house is less conducive. Abstrak Pandemi Covid-19 sangatberpengaruhsekaliterhadapperkembanganpendidikan di Indonesia. Pendidikan di Indonesia memberlakukan program pembelajaranjarakjauh (PJJ) selamapandemi covid-19.Pembelajaranjarakjauhinidiberlakukandengantujuan agar mengurangipenyebaran virus covid-19.Tujuanpenelitianiniadalahmendeskripsikantentangdampakpembelajaranjarakjauhterhadappembelajaransiswa di RA Darul Quran MeguGedeKabupaten Cirebon.Penelitianinimenggunakanpenelitiankualitatifdeskriptif.Teknikpengumpulan data menggunakanobservasi, wawancara dan dokumentasi.Berdasarkan hasil penelitian, pembelajaranjarakjauhmempunyaidampakpositifdandampak negative terhadappembelajaransiswa. Dampakpositifdiantaranya anak mempunyaibanyakwaktuuntukbelajar di rumahbersamakeluarga, anak belajartentangteknologi.Selain itu terdapat beberapa dampak negatif pembelajaranjarakjauh (PJJ) yaitu,anak sulitkonsentrasi, anak lebihmudahjenuh, anak cenderungmerasabosankarena orang tuacenderungmenuntut anak untukbisamemahamipembelajaran, anak lebih suka bermain dibandingkan belajar,dansiswatidaksecaramaksimalmenerimamateripembelajarankarenaguru kurangpersiapandalammemberikanpembejaranjarakjauhsertakeadaanrumah yang kurangkondusif.